Smart cities : blockchain-based system, networks, and data - Gao, Jianbin; Xia, Qi; Asamoah, Kwame Omono; Adjei-Arthur, Bonsu (Boca Raton : CRC Press, 2022)
"Smart Cities: Blockchain-Based Systems, Networks, and Data examines the various components that make up a smart city. It focuses on infrastructure, processes, and services, and outlines approaches for services such as health, transport, energy, and more. With an underlying emphasis on blockchain networks, the authors examine ways to provide the management of resources and activities by creating a more secure and trustless operating systems where resources are more effectively allocated and managed"--
Blockchain and smart city fundamentals -- Infrastructure -- Identities -- Supply chain -- Smart transportation -- Smart health -- Smart city contracting -- Smart energy -- Tokenization of energy systems -- Smart city governance.
OCLC-licensed vendor bibliographic record.
Keywords: Smart cities; Blockchains (Databases); Infrastructure (Economics); City planning -- Data processing; TECHNOLOGY / Construction / Contracting; BUSINESS & ECONOMICS / Decision-Making & Problem Solving